Anticancer Activity of Asiatic Acid from Centella Asiatica: A Comprehensive Systematic Review of In Vitro and In Vivo Studies - Ridho, Fiki Muhammad; Fahrudin, Panggih; Syachputra, Andika Julyanto; Aruan, Iren Angelia; Ulfah, Kamailiya; Syahri, Alfi (Keluwih: Jurnal Kesehatan dan Kedokteran, 2024)
Abstract—Centella asiatica, containing asiatic acid (AsA), represents one such candidate demonstrating promising anticancer effects. This study aims to comprehensively review the anticancer activity of AsA in published in vitro and in vivo studies. A systematic review method was employed and several databases, including Scopus, PubMed, ScienceDirect, and Google Scholar, were used to conduct a comprehensive and systematic search of the literature based in vitro and in vivo studies in November 2023 following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Thirty-three articles were included, distributed across twenty-five in vitro studies, three in vivo studies, and five both in vitro and in vivo studies. Based on the findings in the reviewed articles, we report that AsA, a triterpene derived from C. asiatica, exhibits anticancer effects demonstrated both in various cancer cell lines and in cancer cell-induced animal model, through several mechanisms, including anti-inflammatory effects, antioxidant effects, inhibition of cell proliferation, inhibition of invasion and migration, and induction of apoptosis and autophagy. Conclusions based on findings in in vitro and in vivo studies, AsA has strong potential to be used and developed as an inhibitor of various types of cancer cells. Keywords: anticancer, asiatic acid, cancer, centella asiatica, herbal Abstrak—Centella asiatica, yang mengandung asam asiatik (AsA), mewakili salah satu kandidat yang menunjukkan efek antikanker yang menjanjikan. Penelitian ini bertujuan untuk meninjau secara komprehensif aktivitas antikanker AsA dalam studi in vitro dan in vivo. Metode yang digunakan adalah tinjauan sistematis pada beberapa basis data, termasuk Scopus, PubMed, ScienceDirect, dan Google Scholar, untuk melakukan pencarian literatur yang komprehensif dan sistematis berdasarkan studi in vitro dan in vivo yang dilakukan pada November 2023 dan mengikuti pedoman Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Tiga puluh tiga artikel diinklusikan, terdiri dari dua puluh lima studi in vitro, tiga studi in vivo, dan lima studi in vitro dan in vivo. Berdasarkan temuan dalam artikel yang ditinjau, kami melaporkan bahwa AsA, triterpen yang berasal dari C. asiatica, menunjukkan efek antikanker baik di berbagai sel kanker maupun pada model hewan yang diinduksi sel kanker, melalui beberapa mekanisme, termasuk efek antiinflamasi, efek antioksidan, penghambatan proliferasi sel, penghambatan invasi dan migrasi, serta induksi apoptosis dan autofagi. Kesimpulan berdasarkan temuan dalam studi in vitro dan in vivo, AsA memiliki potensi yang kuat untuk digunakan dan dikembangkan sebagai penghambat berbagai jenis sel kanker. Kata kunci: antikanker, asam asiatik, kanker, centella asiatica, herbal